Peta Riset Pendidikan Guru Pendidikan Anak Usia Dini Universitas Negeri Medan: Analisis Bibliometrik - Artha Mahindra Diputera; Suri Handayani Damanik; Srinahyanti Srinahyanti; May Sari Lubis (Jurnal Pustaka Ilmiah, 2025)
This study aims to map the research focus of undergraduate theses from the Early Childhood Teacher Education program at Universitas Negeri Medan between 2019 and 2023. The goal is to address topic saturation and identify emerging trends. Utilizing a qualitative bibliometric literature review method, 158 theses were collected from the Digilib Unimed repository and analyzed using VOSviewer, generating network and overlay visualizations of keywords. The co-occurrence analysis identified five main clusters. Dominant foci include the development of children aged 5-6 years (cognitive abilities, listening skills, gross motor skills) and parental upbringing styles. Other clusters highlight the roles of teachers, fine motor skills, numeracy development through learning media, and the adaptation of education to the digital era (online learning, child independence, and parental roles). Trend analysis, specifically through overlay visualization, revealed the emergence of new research foci such as speech delay, smartphone impact, collage, YouTube application, language ability, flash cards as media, lesson planning, science learning, and creativity, while older topics tend to show saturation. The interconnections among keywords demonstrate the interdisciplinary nature of early childhood education. In conclusion, despite the saturation in some core research areas, this study uncovers a shift towards new and relevant trends. These findings are expected to guide innovative research and align the study program's research roadmap for the future.